1997
DOI: 10.1046/j.1365-2168.1997.02516.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized study of laparoscopic versus open colonic resection for adenocarcinoma

Abstract: Laparoscopic colonic resection is an acceptable and safe alternative to open procedures; the differences between the two techniques are not marked.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
228
2
16

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(267 citation statements)
references
References 40 publications
21
228
2
16
Order By: Relevance
“…Conversely, issues have arisen with regard to the high proportion of patients who require a conversion to an open procedure, and the generally longer theatre time required with costs associated with them. However, despite advocates of this technique, few have been subjected to randomised controlled clinical trials of therapy (Stage et al, 1997;Hewett et al, 1998;Lacy et al, 2002). Nonrandomised studies have examined cost, some of which have indicated lower costs with laparoscopic surgery (Bokey et al, 1996;Philipson et al, 1997), while others have found the results to be equivocal (Falk et al, 1993;Bergamaschi and Arnaud, 1997;Joo et al, 1998;Khalili et al, 1998;Young-Fadok et al, 2001).…”
mentioning
confidence: 99%
“…Conversely, issues have arisen with regard to the high proportion of patients who require a conversion to an open procedure, and the generally longer theatre time required with costs associated with them. However, despite advocates of this technique, few have been subjected to randomised controlled clinical trials of therapy (Stage et al, 1997;Hewett et al, 1998;Lacy et al, 2002). Nonrandomised studies have examined cost, some of which have indicated lower costs with laparoscopic surgery (Bokey et al, 1996;Philipson et al, 1997), while others have found the results to be equivocal (Falk et al, 1993;Bergamaschi and Arnaud, 1997;Joo et al, 1998;Khalili et al, 1998;Young-Fadok et al, 2001).…”
mentioning
confidence: 99%
“…Pneumoperitoneum, for contributing to a phenomenon called aerosolization, is the most questioned factor for this fact 39,66,70,73,74,78,81,94 . However, the relation between pneumoperitoneum and the forms of tumor cell dissemination and tumor implantation is not clear 4,11,33,41,43,45,49,54,68 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the incidence of tumor implantation in surgical incision is real, after the laparoscopic resection of a carcinoma, it is not definitively establis hed 4,11,33,41,43,45,49,54,68 , estimated to be within the range of 0 to 21% 67,71,76 . However, recent studies report values of 0.6 to 0.7 of incisional tumor recurrence after laparotomy 43,52,57,59 .…”
Section: Vol 32 Nºmentioning
confidence: 99%
See 1 more Smart Citation
“…The complication rate in laparoscopic colorectal surgery is not higher than in open surgery (14)(15)(16). In previous studies, the complication rates were found to be between 1.5-36% (17)(18)(19).…”
mentioning
confidence: 99%